2021
DOI: 10.1016/j.celrep.2021.109514
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef interacts with the cyclin K/CDK13 complex to antagonize SERINC5 for optimal viral infectivity

Abstract: SUMMARY HIV-1-negative factor (Nef) protein antagonizes serine incorporator 5 (SERINC5) by redirecting this potent restriction factor to the endosomes and lysosomes for degradation. However, the precise mechanism remains unclear. Using affinity purification/mass spectrometry, we identify cyclin K (CycK) and cyclin-dependent kinase 13 (CDK13) as a Nef-associated kinase complex. CycK/CDK13 phosphorylates the serine at position 360 (S360) in SERINC5, which is required for Nef downregulation of SERINC5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…To understand how SERINC5 is polyubiquitinated, we interrogated the presence of E3 ubiquitin ligases in SERINC5 protein complexes by mass spectrometry. FLAG-tagged SERINC5 was purified from HEK293T cells by an anti-FLAG affinity column and analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS), as we reported 18 . Four independent experiments were conducted from which a total of 25 ubiquitin E3 ligase-associated proteins were identified, which consisted of Cul1, Cul3, and Cul4B (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how SERINC5 is polyubiquitinated, we interrogated the presence of E3 ubiquitin ligases in SERINC5 protein complexes by mass spectrometry. FLAG-tagged SERINC5 was purified from HEK293T cells by an anti-FLAG affinity column and analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS), as we reported 18 . Four independent experiments were conducted from which a total of 25 ubiquitin E3 ligase-associated proteins were identified, which consisted of Cul1, Cul3, and Cul4B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Nef interacts with SERINC5 via its largest intracellular loop 4 (ICL4) 17 . In addition, Nef directs Cyclin K/Cyclin-dependent kinase 13 (CDK13) complex to phosphorylate a serine residue (S360) at SERINC5 in ICL4, which bridges SERINC5 with the adapter protein 2 (AP2) complex via Nef for endocytosis and degradation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of Nef on SERINC5 found that Nef N-terminal region (residues 32 to 39) is crucial for its interaction with SERINC5, while the C-terminal endocytic sorting motif (E 160 xxxLL 165 ) mediates binding with AP2 [ 9 , 28 ]. Furthermore, it has been shown that Cyclin K/Cyclin-dependent kinase 13 (CDK13) complex-mediated phosphorylation of a serine residue (S360) within the intracellular loop 4 (ICL4) of SERINC5 enhances Nef-AP2-SERINC5 interaction [ 29 ]. However, S360 residue is not conserved among SERINCs [ 8 ].…”
Section: Viral Antagonists Of Serinc5mentioning
confidence: 99%
“…Chai et al used affinity purification/mass spectrometry to identify a complex of cyclin K (CycK) and cyclindependent kinase 13 (CDK13) that interacts with Nef to antagonize SERINC5 for optimal viral infectivity (Figure 3②). Mechanistically, the CycK-CDK13 complex phosphorylates the serine at position 360 in SERINC5, resulting in downregulation of SERINC5 from the cell surface (Chai et al, 2021) (Figure 3③).…”
Section: Serinc Proteins and Antagonistic Retroviral Factorsmentioning
confidence: 99%